SEAWATER DESALINATION SYSTEM AND SEAWATER DESALINATION METHOD - OKAWA YUSUKE; KITAMURA KOTARO; NOTO KAZUHIKO (2013)
The present invention provides a seawater desalination system that enables a reduction in the energy required for generating fresh water and that ensures the quality of the generated fresh water.A seawater desalination system (IA) comprises: a sewage-associated reverse osmosis membrane processing means (10A) and a seawater-associated reverse osmosis membrane processing means (20A). The sewage-associated reverse osmosis membrane processing means (10A) subjects sewage (W10) to membrane separation treatment for generating sewage-associated permeate (WI I) and sewage-associated concentrate (W12). The seawater-associated reverse osmosis membrane processing means (20A) subjects a water mixture of the sewage-associated concentrate (W12) and collected seawater (W20) to membrane separation treatment for generating seawater-associated permeate (W21) and seawater-associated concentrate (W22) and that has a salt concentration measuring means for measuring the salt concentration of the seawater-associated permeate (W21). The seawater-associated permeate (W21) is supplied to the sewage-associated reverse osmosis membrane processing means (10A) according to the salt concentration of the seawater-associated permeate (W21).